Growth Recovery Among HIV-infected Children Randomized to Lopinavir/Ritonavir or NNRTI-based Antiretroviral Therapy. Issue 12 (December 2016) - Achan, Jane; Kakuru, Abel; Ikilezi, Gloria; Mwangwa, Florence; Plenty, Albert; Charlebois, Edwin; Young, Sera; Havlir, Diane; Kamya, Moses; Ruel, Theodore
Abstract : Background: Diminished growth is highly prevalent among HIV-infected children and might be improved by antiretroviral therapy (ART). We examined growth recovery in a rural Ugandan cohort of HIV-infected children randomized to lopinavir/ritonavir (LPV/r) or non nucleoside reverse transcription inhibitor-based ART. Methods: HIV-infected children 2 months to 6 years of age were randomized to LPV/r- or non nucleoside reverse transcription inhibitor-based ART. Changes in weight-for-age (WAZ), height-for-age (HAZ) and weight-for-height Z-scores for 24 months were evaluated using generalized linear repeated measures models. Recovery from being underweight (WAZ<−2), stunted (HAZ<−2) and wasted (weight-for-height <−2) to Z-scores greater than −2 was also compared by arm using Kaplan–Meier survival and Cox proportional hazard modeling. Results: A total of 129 children with median age of 3 years initiated therapy; 64 received LPV/r-based and 65 non nucleoside reverse transcription inhibitor-based ART (nevirapine: 36 and efavirenz: 29). The median (interquartile range) difference in growth measures between baseline and 24 months for LPV/r (n = 45) versus non nucleoside reverse transcription inhibitor-based therapy (n = 40) were as follows: WAZ, 0.47 (0.10, 1.62) versus 0.53 (0.03, 1.14) ( P = 0.59) and HAZ, median 1.55 (0.78, 1.86) versus 1.19 (0.62, 1.65) ( P = 0.23), respectively. ART regimen was not predictive of change in WAZ ( β : −0.02, 95% confidence interval: −0.25, 0.20) or HAZ ( β : 0.05, 95% confidence interval: −0.10, 0.19). The presence of confirmed virologic failure was not associated with growth. Conclusions: Most ART-naive children experienced recovery of both WAZ and HAZ over the 24 months after ART initiation, with no significant difference between those receiving LPV/r versus non nucleoside reverse transcriptase inhibitor-based ART. However, the persistence of median Z-scores below 0 underscores the need for additional strategies to improve growth outcomes in HIV+ African children.